Transformasi Peran Perempuan di Era Digital: Dari Ibu Rumah Tangga menjadi Pelaku Usaha Online - Sadriani, Andi; Syukur, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the transformation of women's roles from housewives to online entrepreneurs in Makassar City and identify the driving factors and challenges faced in this process. The research approach used was descriptive qualitative with purposive sampling of women transitioning to digital entrepreneurship through platforms such as Instagram, TikTok, and Shopee. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources and methods. The results show that Makassar women have experienced significant social transformations along with the development of digital technology. Social media plays a crucial role in transforming domestic activities into productive economic activities. Key driving factors include economic needs, technological convenience, and social support from family and community. This transformation demonstrates the conversion of social capital into economic capital, as described by Bourdieu and Coleman, where trust and social networks are key forces for women's empowerment. Despite facing challenges such as dual role conflict, limited digital literacy, and limited access to capital, women demonstrate high social resilience by leveraging community networks and local solidarity. This research confirms that women's empowerment in the digital era depends not only on technological mastery, but also on the ability to manage and maintain social capital as a sustainable economic force.